Tourists as commodities in below-cost tours - Chen, Shengrong; Zhu, Jiarui (Annals of tourism research, 2025)
This paper focuses on the commodification of tourists in below-cost tours. With the audience commodity theory from the field of political economy of communication as the analytical framework, we reveal the process of tourists' prosumption. In below-cost tours, the relationship between tourists and travel agencies is collaborative coproduction: Travel agencies obtain profits through tourists' prosumption (primarily visiting and shopping) in designated stores. Tourists thereby become a type of commodity that enables capital to obtain exchange value – tourists as commodities. This study advances the explanatory research on below-cost tours, enriches the literature on prosumption by extending it to tourism research, and demonstrates the spread of commodification in social life through empirical studies. [Display omitted] •This study proposes the concept of tourist commodity.•Tourists have become a type of commodity that enables capital to obtain exchange value in below-cost tours.•It is precisely the prosumption of tourists that makes their commodification possible.•In below-cost tours, the relationship between tourists and travel agencies is collaborative coproduction.